N‐linked glycan profiling of GGTA1/CMAH knockout pigs identifies new potential carbohydrate xenoantigens. (5th September 2013) - Burlak, Christopher; Bern, Marshall; Brito, Alejandro E.; Isailovic, Dragan; Wang, Zheng‐Yu; Estrada, Jose L.; Li, Ping; Tector, A. Joseph
Abstract: Background: The temporary or long‐term xenotransplantation of pig organs into people would save thousands of lives each year if not for the robust human antibody response to pig carbohydrates. Genetically engineered pigs deficient in galactose α1, 3 galactose (gene modified: GGTA1) and N ‐glycolylneuraminic acid (gene modified: CMAH) have significantly improved cell survival when challenged by human antibody and complement in vitro . There remains, however, a significant portion of human antibody binding. Methods: To uncover additional xenoantigens, we compared the asparagine‐linked ( N ‐linked) glycome from serum proteins of humans, domestic pigs, GGTA1 knockout pigs, and GGTA1/CMAH knockout pigs using mass spectrometry. Carbohydrate structures were determined with assistance from GlycoWorkbench, Cartoonist, and SimGlycan software by comparison to existing database entries and collision‐induced dissociation fragmentation data. Results: Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS) analysis of reduced and solid‐phase permethylated glycans resulted in the detection of high‐mannose, hybrid, and complex type N ‐linked glycans in the 1000–4500 m/z ion range. GGTA1/CMAH knockout pig samples had increased relative amounts of high‐mannose, incomplete, and xylosylated N ‐linked glycans. All pig samples had significantly higher amounts of core and possibly antennae fucosylation. Conclusions: We provide for the first time a comparison of the serum protein glycomes of the human, domestic pig, and genetically modified pigs important to xenotransplantation.